Ed 'Doc' Rickett's Laboratory, Cannery Row, Monterey - unknown:::Creator::::::::::::
This photograph of the lab at 800 Cannery Row includes a description and a quote from the novel Cannery Row. The misspelling of Ricketts's name appears on the photograph itself.